Activation of Notch Signaling Is Required for Cholangiocarcinoma Progression and Is Enhanced by Inactivation of p53 In Vivo - El Khatib, Mona; Bozko, Przemyslaw; Palagani, Vindhya; Malek, Nisar P.; Wilkens, Ludwig; Plentz, Ruben R. (PLOS ONE, 2013)
Cholangiocacinoma (CC) is a cancer disease with rising incidence. Notch signaling has been shown to be deregulated in many cancers. However, the role of this signaling pathway in the carcinogenesis of CC is still not fully explored. In this study, we investigated the effects of Notch inhibition by γ-secretase inhibitor IX (GSI IX) in cultured human CC cell lines and we established a transgenic mouse model with liver specific expression of the intracellular domain of Notch (Notch-ICD) and inactivation of tumor suppressor p53. GSI IX treatment effectively impaired cell proliferation, migration, invasion, epithelial to mesenchymal transition and growth of softagar colonies. In vivo overexpression of Notch-ICD together with an inactivation of p53 significantly increased tumor burden and showed CC characteristics. Conclusion: Our study highlights the importance of Notch signaling in the tumorigenesis of CC and demonstrates that additional inactivation of p53 in vivo.